Subciliary and Subtarsal Incision in Management of Zygomatico-Orbital Fracture, A Study on Scar Assessment - Rajesh Kumar, Raza Ali, Syed Aijaz Ali Zaidi, Bhavesh Maheshwari, Khursheed Ahmed, Lajpat, Salman Shams (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate outcome between the subciliary and subtarsal incision in management of zygomatico-orbital fracture in terms of postoperative scar assessment. Subject and Methods: A total 36 patients of either gender, age 21 to 40 years having isolated zygomatico-orbital fracture were selected by consecutive sampling (16 patients in Subciliary and 16 in Sub-tarsal group). Zygomatico-orbital fracture was confirmed by 3D CT scan and Occipitomental view of face. After surgery postoperative scar assessment (Pigmentation, Pliability, Vascularity and height) was performed using Vancouver scar scale. Results: Male participants accounted for 27 (84.4%) of the 32 zygomaticomaxillary complex fractured patients, followed by 5 female patients (15.6% ). With 17 (53.1%) patients, the age group 21-25 years was the most afflicted, followed by 26-30 years with 15 (46.9%) patients and a mean age of 25.59 ± 3.004 years. In all three postoperative weeks, the subtarsal group performed considerably better than the subciliary group in terms of postoperative scar evaluation. Conclusion: Scar formation was higher in subciliary group as compared to subtarsal group